Hybrid Multiuser Equalizer for mmWave Massive MIMO GFDM Systems - Kassam, J.; Miri, M.; Magueta, R.; Castanheira, D.; Silva, A.; Gameiro, A. (2020 12th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2020)
In this paper, we propose a hybrid multiuser equalizer combined with low complexity hybrid precoder for wideband millimeter-wave massive MIMO systems. We consider a generalized frequency division multiplexing (GFDM) modulation scheme, which is a new digital non-orthogonal multi-carrier modulation, aiming to achieve higher spectral efficiency, better control of out-of-band (OOB) emissions, and obtain a reduction in peak to average power ratio (PAPR) compared to OFDM. At the transmitter side, a simple yet efficient pure analog precoder is applied. At the base station, the hybrid multiuser linear equalizer is optimized by minimizing the mean square error between the hybrid approach and the full digital counterpart. The analog phase shifters have constant amplitude being constant over the bandwidth due to the hardware constraints. The results show that the performance of the proposed hybrid scheme is very close to the full digital counterpart as the number of RF chains increases.